A critical assessment of the role of fashion in influencing the travel decision and destination choice. (1st January 2013) - Lewis, Clifford; Kerr, Greg; Burgess, Lois
While the word fashion is often associated with clothing and accessories, the objective of this paper is to argue that as a broader concept, fashion has relevance to tourism. It is argued that fashion can influence behaviour and both the decision to travel, and the destination selected may in some cases be a fashion statement by the traveller. Following discussion as to the meanings and explanations of fashion, a conceptual model is presented having the purpose of demonstrating how fashion can be a moderating variable in the travel decision and destination selection process. The model proposes the influence of fashion on leisure tourism, and is a foundation for future studies to further investigate fashion and tourism.